2010
DOI: 10.1021/jp907724t
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sorption Cycling Kinetic Stability and Microstructure of Single-Walled Carbon Nanotube (SWCNT) Magnesium Hydride (MgH2) Nanocomposites

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 52 publications
3
41
0
Order By: Relevance
“…It was recently found that the addition of a mixture of single-wall carbon nanotubes, amorphous carbon and metal catalyst particles prevents coarsening of Mg particles and grains to a large extent [13]. Compared to the baseline case of milled MgH 2 without additives, grain growth of Mg was slowed by over a factor three by the addition of the carbon mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently found that the addition of a mixture of single-wall carbon nanotubes, amorphous carbon and metal catalyst particles prevents coarsening of Mg particles and grains to a large extent [13]. Compared to the baseline case of milled MgH 2 without additives, grain growth of Mg was slowed by over a factor three by the addition of the carbon mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in absorption and desorption times during cycling was slowed down by a factor three or more for the MgH 2 -SWCNT mixture compared to the baseline. Analysis of the activation energies revealed that the catalytic activity of the metal particles was lost during cycling [13].…”
Section: Introductionmentioning
confidence: 99%
“…35,[73][74][75][76][77] The effect of carbon as additive on the hydrogen release from ball-milled MgH 2 is illustrated in Fig. 5.…”
mentioning
confidence: 99%
“…Thus, in this respect, the HCS+MM-Mg 99 Ni+Nano-nickel/MWCNT is superior to those reported in previous works. 42,43) …”
Section: Rehydrogenation Propertiesmentioning
confidence: 99%